Unlocking copper flotation efficiency: the interaction of Citrobacter sp. strain SKC-4 with chalcopyrite concentrate as a potential eco-friendly reagent alternative - Sanwani, Edy; Wahyuningsih, Tri; Winarko, Ronny; Chaerun, Siti Khodijah (Institut Teknologi Bandung, 2024)
This research explores the viability of bioflotation as an eco-friendly alternative to conventional chemical reagents in processing copper sulfide ores. It primarily focuses on the interactions between bacterial cells and chalcopyrite concentrate. A key objective is to identify bacterial strains suitable for use as bioflotation reagents. The study specifically examines the interaction between Citrobacter sp. strain SKC-4, a bacterium native to sulfur-rich environments, and chalcopyrite (CuFeS2) concentrates over a 30-day period. This bacterium is known for its ability to produce biosurfactants and oxidize iron and sulfur, making it an ideal candidate for various roles in bioflotation, such as biocollectors, biodepressants, and biofrothers. Experimental setups involved mixing chalcopyrite concentrates (-200+325 mesh, 25% w/v) with the bacterial strain (10% v/v) in modified LB media under aerobic conditions with constant shaking. Periodic sampling facilitated subsequent analyses. Results indicated biosurfactant production by the bacteria, as evidenced by the detection of hydroxyl (OH) groups, amine (NH) groups, and glycosidic bonds (C-O-C), along with the identification of hydrophilic C=O groups through FTIR (Fourier transform infrared) analysis, suggesting the presence of biodepressant, biocollector, and biofrother properties. Surface tension measurements consistently showed values below that of water (71 mN/m), supporting the biosurfactants' potential as flotation biofrothers and biocollectors. These findings suggest that employing Citrobacter sp. strain SKC-4 could substantially reduce the environmental impact of using chemical reagents in the flotation process. This study not only proposes a sustainable substitute for traditional flotation reagents but also demonstrates the potential of bioflotation to improve the efficiency and environmental sustainability of copper sulfide ore processing. The adoption of microorganisms as bioflotation reagents could transform the mineral processing industry by minimizing chemical use and environmental impact, contributing to more sustainable mining practices.